Desalination Performance of a Unique Capacitive Deionization Cell Optimized with ANSYS Flow Simulation - Duranoglu, Dilek; Al-Aghbari, Mansoor (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2024)
Capacitive deionization (CDI) is an emerging water treatment method that shows great promise for efficient desalination purposes. It enables the production of purified, potable water by effectively removing ions from seawater and brackish water. In this study, a unique capacitive deionization (CDI) cell design with an expansion part and without a spacer was proposed. It was then optimized using computational fluid dynamics (CFD) with ANSYS 21 (academic version) software to ensure a uniform flow distribution across the electrode surface, thus maximizing the utilization of the electrode. Subsequently, the developed optimum CDI cell was fabricated using 3D printing, and its desalination performance was evaluated in a batch system using NaCl solution. The optimum CDI cell design enhanced the salt adsorption capacity of the process by 47% compared to the first proposed design. The effect of operating parameters like potential, flow rate, and time on the salt adsorption capacity were investigated with the optimum CDI cell design. The maximum salt adsorption capacities were approximately 2.9 mg/g, 6.0 mg/g, and 14.7 mg/g for 2 mM, 20 mM, and 200 mM NaCl concentrations, respectively, at a potential of 1.2 V, a flow rate of 20 mL/min, and an adsorption/desorption period of 15 min. The electrodes exhibited a stable performance and full regeneration over long adsorption/desorption cycles. The findings of this study highlight the effectiveness of the proposed CDI cell design in enhancing salt removal efficiency. These results contribute to the advancement of water treatment technologies by providing insights into optimizing CDI processes for more efficient and sustainable desalination operations.
Keywords: Capacitive deionization (CDI); Desalination; Optimization; Flow simulation; CARBON AEROGEL; DESIGN; ELECTROSORPTION; ELECTRODES; ENERGY; OXIDE; Chemistry; Engineering